BEBERAPA SIFAT DASAR DAN KEGUNAAN TIGA JENIS KAYU KURANG DIKENAL ASAL HUTAN ALAM SULAWESI - Mody Lempang; Muhammad Asdar (Jurnal Penelitian Hasil Hutan, 2012)
This research was carried out to cocamine hatic wood properties (anatomical structure, physical and mechanical properties and machining aspect of three lesser-known species from natural forest in Sulawesi ie. sama-sama (Ponteria firma Bachni), palade (Aglaia sp.) and kumsa batu (Manilkaru merrilliana H.J.L.). Appropirate pood utulization war determined by considering their basic properties and uses which the locally community bave currently end Results revealed that sama-sama beartwood is dark brown to black with irregular black lines bandi; rather fine texture and glasry surface; rather beary; moderate in dimenzional shrinkage; strenght class IV-III; good grade for machinery, fiber grade is good for pulp/paper manufacture; probable utilization are for light construction material in bouse building and certain ship omponents, peeling venter, glulam, pallet, pulp and paper. Palado beartwood is light brown to grayish brown colour, straight grain; rather fine tecture; rather beavy; moderate in dimensional shrinkage; strenght class III; good grade in machinery, fiber grade is good for pulp/paper manufacture; probable utilization are for light construction material in hours building and certain ship components, cheap furniture, moulding, glaulam, peeling veneer, bandicraft, pulp and paper. Kumna batu beartwood is reddish brown colour, greath rings diffuse and sometimes appeared clear with figures of decurative surface as parallel lines on radial section; grain straight; toctare fine and glosty zarface; remarkably beary, high in dimensional shrinkage; strenght class 11; very good grade in machinery: fiber grade is poor for palp/paper manafactureprobable utilization are for beary construction material in bowse and ship building, vehicular(track bodypower line poles, furniture, moulding, slicing veneer, tool bandies, handicraft and charcoal.